Interactivity on the Website of Monte Carlo International Radio Regarding Iraqi Topics - Abdul Sattar, Hawra Ali; Mohammad, Ammar Taher (ALBAHITH ALALAMI, 2023)
This research aims to identify the means and forms of interactive communication concerning Iraqi topics on the websites of global radio stations, namely Sawa and Monte Carlo. It also seeks to uncover the editorial and artistic interactions related to Iraqi topics on the selected websites chosen as the research sample, comparing them with the editorial interaction within the Iraqi context between the Radio Monte Carlo and Sawa websites.The research yields several conclusions, including the following:Iraqis focus their interaction with topics related to Iraq on Facebook for both Radio Monte Carlo and Sawa; Arabs show higher levels of interaction on Twitter with Radio Monte Carlo; Participants on the websites of both Radio Sawa and Monte Carlo distribute themselves concerning Iraqi topics as supporters, neutral observers, and protesters. In comparison to comments and sharing, 'liking' is the predominant form of communication used for interacting with topics related to Iraq on both the Radio Monte Carlo and Sawa websites.